Navigating Business Competition In The Endemic Era: Marketing Strategies At Pandawa Resort Nusa Penida - Desak Made Febri Purnama Sari; Suningsih, Ni Luh; Rukmiyati, Ni Made Sri (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
The COVID-19 pandemic has significantly impacted the tourism industry, prompting a need to investigate effective marketing strategies in the endemic era. This qualitative study examines the utilization of the marketing mix (7Ps) at Pandawa Resort and Seaview Nusa Penida to address business competition. Through observation, interviews, and documentation, data were collected from seven informants. The findings indicate that Pandawa Resort offers diverse room options with comprehensive amenities, implementing five key marketing strategies. These include product diversification to meet customer preferences, streamlined booking processes, strategic location selection, effective human resource management through employee training and local hiring, and creating a comfortable, modern environment. The study underscores the importance of each marketing mix element in enhancing hotel competitiveness, particularly amidst the endemic era's challenges. However, there is room for improvement in the promotion strategy, which currently falls short in capturing consumer attention. Enhancements in this area are crucial for bolstering the competitive edge of Pandawa Resort and Seaview Nusa Penida in the hotel market.